Transformation of Tourism Administration: Integration of Slow Tourism and Waste Management in Protecting Bali's Heritage Towards SDG Target - Ida Ayu Putri Riandari; Nyoman Diah Utari Dewi; Ni Putu Tirka Widanti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Abstract This study examines the role of public administration in managing the challenges of urban tourism in Bali, particularly those related to the waste crisis and the degradation of cultural heritage. Amid increasing pressure on urban infrastructure, the paradigms of Slow Tourism and Soft Tourism have emerged as alternative policy strategies to advance the Sustainable Development Goals (SDGs), especially SDGs 11 and 12. Employing a descriptive qualitative method through a literature review and policy observation conducted between 2024 and 2026, the study evaluates the effectiveness of the tourist levy policy and decentralized waste management programs in Bali. The findings indicate that rigid tourism bureaucracies frequently hinder the integration of cultural heritage preservation with modern waste management systems. The study concludes that transforming public administration through a collaborative governance model is essential to shift tourist behavior from mass consumption toward more immersive travel experiences (slow travel). This transformation has been shown to significantly reduce daily waste volumes while simultaneously increasing the economic value of heritage sites through longer lengths of stay. Keywords: Public Administration, Urban Tourism, Waste and Tourism, Slow Tourism, Bali Heritage.